PENGARUH INDEPENDENSI, INTEGRITAS DAN PROFESIONALISME TERHADAP KUALITAS AUDIT - Siska Yulia Defitri; Juita Sukraini; Yori Irawani (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2022)
This study aims to determine the effect of independence, integrity and professionalism on audit quality. The sample in this study were auditors at the Inspectorate Office of Solok City, Solok Regency, Sawahlunto City, and Padang City, totaling 62 respondents. The type of data used is primary data. The sample technique used is saturated sample by distributing questionnaires.The results showed that: (1) independence has a positive and significant effect on audit quality. This is evidenced by using the t test with a t-count value greater than the t-table of 3,312> 2.00172. (2) Integrity does not have a positive and significant effect on audit quality. This is evidenced by using the t test with a t-value greater than t-table of 0.372> 2.00172. Besides, it has a significant value of 0.711> 0.05. (3) Professionalism has a direct effect on audit quality. This is evidenced by the t test, namely t count of 5.744> t table of 2.00172 with a significance of 0.000 <0.05. (4) independence, integrity and professionalism affect audit quality. This is evidenced by the calculated F value of 36.390> from the F table, which is 2.76 or the F significance level of 0.000 <0.05.